Enhancement of high-quality cinnamon quill production through agronomic approaches: a review - Hashitha Nayananjalee Aluthgamage; D.L.C. Kumari Fonseka; Niluka Nakandalage (Academia Biology)
Cinnamon is a well-recognized invaluable spice used worldwide throughout centuries for numerous purposes. Sri Lankan history has been greatly influenced by the cinnamon trade as the birthplace of this valuable crop. Even today, cinnamon plays an important role in the Sri Lankan economy, being the fourth export agricultural crop that acquires a considerable amount of foreign exchange to the country. Although a considerable amount of foreign exchange is earned through the cinnamon trade, the existing potential is still under-exploited. Low productivity of cinnamon lands and lower-grade cinnamon quills have been identified as major bottlenecks to prevent reaching the potential income. The majority of cinnamon is exported as quills. Therefore, the objective of this review was to gather available literature and formulate a comprehensive analysis of three main aspects considering the quantitative and qualitative enhancement of cinnamon quill production, namely yield indices, bush architecture, and type of planting materials. According to the literature, the productivity of cultivations can be enhanced by optimizing one or more yield indices of cinnamon. At the same time, stems suitable for producing higher-grade quills can be obtained by optimizing the bush architecture. Simultaneously, the optimum conditions for higher productivity and quality can differ for seedlings and vegetatively propagated plants.